Bones. The complete tenth season [videorecording (DVD)] - Hanson, Hart (20th Century Fox Home Entertainment, 2015)
In the Tenth Season, suspense is at an all-time high as Booth is framed and jailed for the murder of three FBI agents while Bones considers committing blackmail to get him out of prison. Meanwhile, the team at the Jeffersonian sets out to solve a whole new roster of bizarre cases, the deaths of a controversial radio host, a mysterious crossword puzzler, and many more.